Trust in Government and Social Media Competence as Primary Drivers: Examining CitizensʼIntentions to Adopt Digital Government Applications for Risk Management - Lee, Tae Jun (KDI School of Public Policy and Management, 2020)
Building upon a framework of the unified theory of acceptance and use of technology (UTAUT), this study explores the determinants of citizens’ intentions to use the government’s mobile application for risk communication. An online survey was conducted with a quota sample of 700 Korean citizens. The results from structural equation modeling suggest that social media competence and trust in government information are primary determinants of willingness to accept the new application and intention to use it. Trust in government information appeared to influence the acceptance of the application both directly and indirectly through performance expectancy and effort expectancy. More confidence in the use of social media led to higher levels of performance expectancy, effort expectancy, and facilitating conditions, all of which subsequently contributed to willingness to accept the application. The acceptance of the application further influenced intention to use the application and the likelihood of positive recommendations. The findings suggest that while developing applications that meet public expectations for informational benefits and time efficiency is important, it is also necessary for the government to build trust and improve citizens’ ability to use new tools in order for new information technology initiatives to fully benefit citizens.